208k views
14 votes
(h+1)^2=16 solve using square root property

2 Answers

9 votes

Answer: h = 3

Explanation:

(h+1)² = 16

h+1 = √16

h+1 = 4

h = 3

Hope this helped :)

User Juanferrer
by
4.1k points
7 votes

Answer:


h=3, \ h=-5

Explanation:


(h+1)^2=16


(h+1)^2=16


√((h+1)^2) = \±√(16) <== you take the square root of both sides


(h+1) = \±\ 4 <== you take the square root of both sides


(h+1) = +\ 4, \ (h+1) = -\ 4 <== separate into 2 equations and solve


h+1 = 4, \ h+1 = -\ 4\\\\. \ -1 -1, \ \ \ \ -1\ \ \ \ -1\\\\h=3, \ h=-5

Hope this helps!

User NetanZaf
by
5.3k points